Photovoltaic system faults detection using fractional multiresolution signal decomposition - Lanani, A.; Djamai, D.; Beddiaf, A.; Saidi, A.; Abboudi, A. (Національний технічний університет "Харківський політехнічний інститут", 2024)
In this paper, we present an innovative methodology based on fractional wavelets for detecting defects in photovoltaic systems. Photovoltaic solar systems play a key role in the transition to a low-carbon economy, but they are susceptible to various defects such as microcracks, wiring faults, and hotspots. Early detection of these anomalies is crucial to prevent energy losses and extend the lifespan of installations. Novelty of the proposed work resides in its pioneering nature, leveraging a family of fractional wavelets, with a specific emphasis on fractional Haar wavelets. This approach enhances sensitivity in anomaly detection, introducing a fresh and promising perspective to enhance the reliability of photovoltaic installations. Purpose of this study is to develop a defect detection methodology in photovoltaic systems using fractional wavelets. We aim to improve detection sensitivity with a specific focus on low-amplitude defects such as microcracks. Method. Our innovative methodology is structured around two phases. Firstly, we undertake a crucial step of filtering photovoltaic signals using fractional Haar wavelets. This preliminary phase is of paramount importance, aiming to rid signals of unwanted noise and prepare the ground for more precise defect detection. The second phase of our approach focuses on the effective detection of anomalies. We leverage the multiresolution properties of fractional wavelets, particularly emphasizing fractional Haar wavelets. This step achieves increased sensitivity, especially in the detection of lowamplitude defects. Results. By evaluating the performance of our method and comparing it with techniques based on classical wavelets, our results highlight significant superiority in the accurate detection of microcracks, wiring faults, and hotspots. These substantial advances position our approach as a promising solution to enhance the reliability and efficiency of photovoltaic installations. Practical value. These advancements open new perspectives for preventive maintenance of photovoltaic installations, contributing to strengthening the sustainability and energy efficiency of solar systems. This methodology offers a promising solution to optimize the performance of photovoltaic installations and ensure their long-term reliability.

У статті ми представляємо інноваційну методологію, засновану на дробових вейвлетах для виявлення дефектів у фотоелектричних системах. Фотоелектричні сонячні системи відіграють ключову роль у переході до низьковуглецевої економіки, але вони схильні до різних дефектів, таких як мікротріщини, несправності проводки та гарячі точки. Раннє виявлення цих аномалій має вирішальне значення для запобігання втратам енергії та продовження терміну служби установок. Новизна запропонованої роботи полягає у її новаторському характері, в якій використовується сімейство дробових вейвлетів з особливим упором на дробові вейвлети Хаара. Цей підхід підвищує чутливість виявлення аномалій, відкриваючи нову суттєву перспективу для підвищення надійності фотоелектричних установок. Метою дослідження є розробка методології виявлення дефектів у фотоелектричних системах з використанням дробових вейвлетів. Ми прагнемо покращити чутливість виявлення, приділяючи особливу увагу дефектам малої амплітуди, таким як мікротріщини. Метод. Наша інноваційна методологія складається із двох етапів. По-перше, ми робимо вирішальний крок щодо фільтрації фотоелектричних сигналів з використанням дробових вейвлетів Хаара. Цей попередній етап має першорядне значення, оскільки його мета - позбавити сигнали від небажаного шуму та підготувати ґрунт для більш точного виявлення дефектів. Другий етап нашого підходу спрямовано на ефективне виявлення аномалій. Ми використовуємо властивості множини роздільної здатності дробових вейвлетів, приділяючи особливу увагу дробовим вейвлетам Хаара. На цьому етапі досягається підвищена чутливість, особливо у разі виявлення дефектів малої амплітуди. Результати. Оцінюючи ефективність нашого методу та порівнюючи його з методами, заснованими на класичних вейвлетах, наші результати підкреслюють значну перевагу у точному виявленні мікротріщин, несправностей проводки та гарячих точок. Ці суттєві досягнення роблять наш підхід багатообіцяючим рішенням для підвищення надійності та ефективності фотоелектричних установок. Практична цінність. Ці досягнення відкривають нові перспективи для профілактичного обслуговування фотоелектричних установок, сприяючи підвищенню стійкості та енергоефективності сонячних систем. Ця методологія пропонує багатообіцяюче рішення для оптимізації продуктивності фотоелектричних установок та забезпечення їхньої довгострокової надійності.
Keywords: fault detection; photovoltaic systems; microcracks; wiring defects; hot spots; preventive maintenance; multiresolution analysis; fractional wavelets; виявлення несправностей; фотоелектричні системи; мікротріщини; дефекти проводки; гарячі точки; профілактика; множинний аналіз; дробові вейвлети